Buletin Peternakan : Effect of Phosphate Fertilizer and Arbuscular Mycorrhizal Fungi on The Nutrient, Phosphateuptake and in Vitro Digestibility of Alfalfa - Bambang Suwignyo, Bela Putra, Nafiatul Umami, Cahyo Wulandari, Ristianto Utomo (Peternakan UGM, 2016)
This study aimed to determine the effect of arbuscular mycorrhizal fungi (AMF) and phosphate (P) fertilizer on the nutrient content, phosphate uptake and in vitro digestibility of alfalfa (Medicago sativa L.)